2023
DOI: 10.3390/molecules28166092
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Metabolic Function of Microbiota during the Washed Processing of Coffea arabica

Xiaojing Shen,
Baijuan Wang,
Chengting Zi
et al.

Abstract: Coffee fermentation is crucial for flavor and aroma, as microorganisms degrade mucilage and produce metabolites. This study aimed to provide a basis for understanding the impact of microorganisms on Coffea arabica from Yunnan, China, during washed processing. The microbial community structure and differentially changed metabolites (DCMs) of C. arabica beans during washed processing were analyzed. The results indicated that the top five predominant microorganisms at the genera level were Achromobacter, Tatumell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…At the taxonomic level, the richness and diversity indices allow the characterization of the whole microbial community; in this case, the largest number of bacterial and fungal species was observed at the beginning of fermentation. This was also observed in recent studies in China, where fermentations were evaluated for 36 h and the highest richness and diversity values for both bacteria and fungi were obtained at the beginning of the process [23]. In this study in particular, Var.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At the taxonomic level, the richness and diversity indices allow the characterization of the whole microbial community; in this case, the largest number of bacterial and fungal species was observed at the beginning of fermentation. This was also observed in recent studies in China, where fermentations were evaluated for 36 h and the highest richness and diversity values for both bacteria and fungi were obtained at the beginning of the process [23]. In this study in particular, Var.…”
Section: Discussionsupporting
confidence: 86%
“…These factors also influence the fermentation stage because changes within the same process, such as the consumption of some nutrients and changes in pH and temperature, modify the structures of the microbial population [22]. In addition, the microorganisms metabolic functions can vary according to the interaction with other microorganisms present in the fermentation environment [23]. Although some research has concluded that the presence of microbial species during the fermentation process varies mainly by the region where the process takes place [7,11], the role that coffee variety could play in influencing the microbiological characteristics of fermentation has not been sufficiently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one potential pathway is that bug damage to the coffee plant creates favorable conditions for microorganisms, with research highlighting that bacteria and fungi found on PTD-affected coffee beans produced IPMP as a metabolite [12][13][14]. Previous research has shown that the presence of microorganisms on coffee beans can cause the concentration of various compound classes like hydrocarbons, phenols, ketones, and aldehydes in coffee to increase [3,63,64]. These types of compounds can form by microorganisms oxidizing the lipids naturally present in the coffee beans [3].…”
Section: Tablementioning
confidence: 99%